Passivity-based control design for a grid-connected hybrid generation system integrated with the energy management strategy. (February 2019) - Patrone, M.; Feroldi, D.
Highlights: The power electronic converters are modelled using the Euler–Lagrange equations. The power controllers are synthesized via passivity-based control. The error dynamics of the closed-loop system are asymptotically stable to zero. The energy management strategy is integrated with the power controllers. The controlled variables show good tracking response under different scenarios. Abstract: Hybrid generation systems produce electric energy from a wide variety of energy sources, including renewable sources. A hybrid system based on renewable sources usually consists of two or more renewable energy sources with the possibility of including storage units so as to enhance the reliability of the system. The hybrid system requires an energy strategy that determines the operation point of each element of the system depending on multiple variables and subjected to the constraints inherent in this kind of systems. In addition, the system needs controllers to command each of these elements in order to reach the operation point established by the energy strategy. Here, we propose a control design via passivity-based control integrated with an energy management strategy for a hybrid generation system based on solar energy and coupled with the grid. The performance of the control methodology is extensively assessed through computer simulation using a comprehensive nonlinear model of the plant. The results show that the controlled system accomplishes the control tasks with good responses, working under very different atmospheric conditions and required load power.